STK11 alterations in the pan-cancer setting: prognostic and therapeutic implications. (May 2021) - Krishnamurthy, Nithya; Goodman, Aaron M.; Barkauskas, Donald A.; Kurzrock, Razelle
Abstract: Background: STK11 is an important tumour suppressor gene reported to confer immunotherapy resistance in non–small-cell lung cancers (NSCLC) especially in the presence of KRAS co-alterations. Methods: This study analysed 4446 patients for whom next-generation sequencing of tissue and/or circulating tumour DNA (ctDNA) had been performed. Results: Overall, 60 of 4446 tumours (1.35%) harboured STK11 alterations. STK11 alterations were associated with shorter median time to progression and overall survival (OS) across cancers from diagnosis: 6.4 months (5.1–7.9) versus 12 months (11.7–12.3; p = 0.001); and 20.5 (17.4–23.5) versus 29.1 (26.9–31.3; p = 0.03), respectively (pan-cancer). Pan-cancers, the median progression-free survival (PFS; 95% CI) for first-line therapy (regardless of treatment type) for those with co-altered STK11 and KRAS (N = 27; versus STK11 -altered and KRAS wild type [N = 33]), was significantly shorter (3 [1.3–4.7] versus 10 [4.9–15.7] months, p < 0.0005, p multivariate, 0.06); the median OS also was also shorter (p multivariate = 0.02). In pan-cancer patients treated with checkpoint blockade, STK11 and KRAS co-altered versus STK11 -altered/ KRAS wild type had a shorter median PFS and trend toward shorter OS (p = 0.04 and p = 0.06, respectively). In contrast, in examining STK11 -altered versus wild-type pan-cancer patients treated with checkpoint blockade immunotherapy, the two groups showed no difference in outcome (PFS [p = 0.4]; OS [p = 0.7]); STK11 -altered versus wild-type lung cancer patients also did not fare worse on immunotherapy. Conclusions: Across cancers, STK11 alterations correlated with a poor prognosis regardless of therapy. However, STK11 alterations alone did not associate with inferior immunotherapy outcome in the pan-cancer setting or in NSCLC. Pan-cancer patients with co-altered STK11/KRAS did worse, regardless of treatment type. Highlights: STK11 alterations had shorter median time to progression and overall survival (OS). Pan-cancer co-altered STK11 / KRAS did worse, regardless of treatment type. STK11 alterations alone did not associate with inferior immunotherapy outcome. STK11 and KRAS and TP53 mutations had a significantly shorter PFS and OS.